Study on the Synthesis of CPAM Paper Reinforcing Agent in Aqueous Two-Phase System - Huang, Chongxing; Yan, Mengmeng; Jiang, Yong; Yang, Qifeng; Chen, Ying; Wang, Shuangfei (Asian Journal of Chemistry, 2012)
In this paper, low molecular weight CPAM paper reinforcing agent was synthesized in aqueous two-phase system by using acrylamide (AM) and methacryloyloxy ethyl trimethyl ammonium chloride (DMC) as the main raw material and the effects of monomer concentration, monomers mole ratio, initiator concentration, dispersant concentration, reaction temperature and reaction time on the CPAM paper reinforcing agent performance were mainly discussed by single factor experiments. Moreover, the molecular structure of CPAM was also identified by IR and NMR analysis. The results showed that the optimum process of the CPAM synthesized with AM and DMC in aqueous two-phase system are as follows: monomer concentration 25 %, the mole ratio of AM and DMC 1:3, PEG concentration 1 %, initiator concentration 0.15 % ( the mass ratio of ammonium persulfate and urea 1:1), reaction of initial temperature for 35 ºC, reaction time 6 h, NaCl concentration 10 % and stirring speed 180 r/min.